Using MIQUEST in General Practice - Victoria Hammersley; Andrew Meal; Lynne Wright; Mike Pringle (Journal of Innovation in Health Informatics, 1998)
This paper describes ten months' experience with MIQUEST software used for the collection of data from computerised databases in General Practice. We report on the following: the MIQUEST software in use, the time costs to the practice, the completeness of confidentiality barriers and the accuracy of data collected using MIQUEST compared with similar data collected by the practice system (EMIS). There were no problems encountered with installation of MIQUEST-related software. With experience, MIQUEST was equal to the practice system for speed and ease of use. The confidentiality safeguards were found to be in accordance with the GMSC/RCGP Guidelines - patients could not be directly, or indirectly, identified from the data extracted by external searches. Inaccuracies in the data collected using MIQUEST were identified, but these were largely attributable to problems with the EMIS-written interpreter available on the practice system at the time, or with the coding schemes used by the practice. In an individual practice, MIQUEST represents an alternative data collection method to the practice-based software. For data collection from multiple general practices it should prove an invaluable tool for Health Authorities and research organisations.